Molecular mechanisms of quinolone-resistant uropathogenic Escherichia coli strains - Horna-Ruíz, Ana M. (2013)
The use of quinolones for the treatment of urinary tract infections (UTI) has increased dramatically, a fact that has led to the emergence of resistant strains of pathogen. The aim of the study was to determine the profiles and molecular mechanisms of quinolone-resistant uropathogenic Escherichia coli strains. For this, 3 sensitive strains of E. coli uropathogenic and 58 quinolone-resistant strains were used in the antimicrobial sensitivity with the disk diffusion method for nalidixic acid (W), ciprofloxacin (Cip), levofloxacin (Lvx), norfloxacin (Nfx) and moxifloxacin (Mxf). For molecular tests were used polymerase chain reaction (PCR), restriction fragments length polymorphism (RFLP) and sequencing of gyr A gene. Excel, Blastn and ClustalX programs were used for data analysis. Uropathogenic E. coli strains showed two major patterns: 25,90% resisted W and 43,10% resisted WCipNorLvxMxf. RFLP-PCR of gyr A gene showed that 50 (86,20%) strains had a point mutation in codon 83 wich changed Ser by Leu in the DNA gyrase A, while four strains did not have this mutation. With the analysis of nucleotide sequences of gyr A gene from 26 strains were confirmed restriction patterns; besides, 22 strains a mutation changed Asp 87 to Asn. Uropathogenic E. coli strains resistant to WCipNorLvxMxf represented the main pattern of quinolone resistance. Also, most strains contain a mutation in the DNA gyrase A changing Ser 83 by Leu.